Strength Profile of Hip Abductor and Adductor Muscles in Youth Elite Soccer Players - Karatrantou, Konstantina (J Hum Kinet, 2019)
The main objective of this study was to provide an extensive isokinetic profile of the hip joint in youth soccer players, where the literature is limited. Additionally, this study investigated the effect of age on isokinetic peak torque values of hip abductor and adductor muscles and on reciprocal muscle group torque ratios in youth soccer players at different angular velocities (30 vs. 90o/s) and muscle actions (concentric vs. eccentric). Sixty young elite male soccer players were assigned into three equal groups (n = 20): children, young adolescents and older adolescents, and performed five maximal concentric and eccentric hip-abductions and adductions at 30o/s and 90o/s. The results showed a significant increase (p < 0.05) in peak torque values from childhood to adolescence, with the exception of young adolescents vs. older adolescents where no differences were observed. The reciprocal ratios were not affected by age, but improved with an increase in angular velocity with the exception of the CON/ECC ratio that was higher at 30o/s. The data presented in this study provide an extensive isokinetic profile of hip abductor and adductor muscle strength in youth soccer players to assist both coaches and sports medicine professionals in strength monitoring and training.